Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 176164 by HeferH last updated on 14/Sep/22

 Proof that :      (√((1 − cos x)/(1 + cos x))) + (√((1 + cos x)/(1 − cos x))) = 2 ∙ cosec x

Proofthat:1cosx1+cosx+1+cosx1cosx=2cosecx

Answered by Rasheed.Sindhi last updated on 14/Sep/22

 (√((1 − cos x)/(1 + cos x))) + (√((1 + cos x)/(1 − cos x))) = 2 ∙ cosec x  LHS:((√(1 − cos x))/( (√(1 + cos x))))+((√(1 + cos x))/( (√(1 − cos x))))          =((1−cos x+1+cos x)/( (√(1−cos^2 x))))         =(2/(sin x))         =2∙(1/(sin x))          =2cosec x=RHS

1cosx1+cosx+1+cosx1cosx=2cosecxLHS:1cosx1+cosx+1+cosx1cosx=1cosx+1+cosx1cos2x=2sinx=21sinx=2cosecx=RHS

Terms of Service

Privacy Policy

Contact: info@tinkutara.com